2010
DOI: 10.1111/j.1466-8238.2010.00545.x
|View full text |Cite
|
Sign up to set email alerts
|

What drives the positive correlation between human population density and bird species richness in Australia?

Abstract: Aim To test six hypotheses that could explain or mediate the positive correlation between human population density (HPD) and bird species richness while controlling for biased sampling effort. These hypotheses were labelled as follows: productivity (net primary productivity, NPP); inherent heterogeneity (diversity of vegetation types); anthropogenic heterogeneity (diversity of land uses); conservation policy (proportion of conservation land); increased productivity (humaninduced productivity increases); and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
34
1
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(38 citation statements)
references
References 48 publications
(74 reference statements)
1
34
1
2
Order By: Relevance
“…Sin embargo, a extensiones más regionales también emergen correlaciones de signo negativo (véase el estudio de Koh et al 2006 en el norte de Taiwán). Finalmente, para la región de Australia, únicamente se han realizado dos estudios hasta el momento, a un tamaño de grano de 1º x 1º y a nivel de ecorregiones (Luck et al 2004(Luck et al , 2010. Aunque todos los taxones de tetrápodos están representados en estas dos publicaciones, la escasez de trabajos para esta región sugiere una clara necesidad de realización de estudios futuros, sobre todo a escalas regionales.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Sin embargo, a extensiones más regionales también emergen correlaciones de signo negativo (véase el estudio de Koh et al 2006 en el norte de Taiwán). Finalmente, para la región de Australia, únicamente se han realizado dos estudios hasta el momento, a un tamaño de grano de 1º x 1º y a nivel de ecorregiones (Luck et al 2004(Luck et al , 2010. Aunque todos los taxones de tetrápodos están representados en estas dos publicaciones, la escasez de trabajos para esta región sugiere una clara necesidad de realización de estudios futuros, sobre todo a escalas regionales.…”
Section: Discussionunclassified
“…Con este fin, ha existido un gran interés en documentar la coincidencia espacial entre DPH y riqueza de especies para diferentes grupos taxonómicos y regiones biogeográficas. Por ejemplo, numerosas publicaciones han mostrado que DPH se correlaciona positivamente con la riqueza de especies para vertebrados terrestres africanos (Balmford et al 2001), en Europa (Araújo 2003), Australia y Norte América (Luck et al 2004(Luck et al , 2010 o para toda una clase taxonómica (Mammalia) a extensión global y regiones biogeográficas (Torres-Romero y Olalla-Tárraga, datos sin publicar). Sin embargo, Pautasso (2007) y Beck et al (2012 sugieren que podría existir un efecto de la escala espacial de análisis (extensión geográfica y tamaño de grano), de tal manera que cabría esperar que la relación negativa entre impacto humano y riqueza de especies fuese más fácilmente detectable a extensiones regionales, y contrariamente una correlación positiva a extensiones más amplias (por ejemplo, continentales y/o globales).…”
Section: Introductionunclassified
“…Another problem with grid cells, but not bioregions, is that they have unequal land area when they span large latitudinal gradients or coastal lines. Luck et al (2010) reported a low correlation between cell size and richness implying that area is not a key factor in driving richness suggesting this sample bias inherent in grids was not an important issue. This conclusion is at odds with our species accumulation analyses, and may reflect that Luck et al (2010) did not control for bioregion.…”
Section: Discussionmentioning
confidence: 99%
“…Luck et al (2010) reported a low correlation between cell size and richness implying that area is not a key factor in driving richness suggesting this sample bias inherent in grids was not an important issue. This conclusion is at odds with our species accumulation analyses, and may reflect that Luck et al (2010) did not control for bioregion. For example, coastal grid cells with small proportion of land cover will have higher richness that grid cells from the arid zone with 100% land cover because of differences in primary productivity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation